Analyzing the relationship between inward FDI, education and entrepreneurial activity at the macro-level - O'Hagan Luff, Martha (My University, 2021)
We investigate the roles of inward FDI and education in explaining country levels of entrepreneurship. It is widely recognised that inward FDI may have positive but also negative spillover effects on entrepreneurial activity. We argue that both types of spillovers (positive and negative) may be reinforced by high education levels of the labour force. Using a database across 75 countries between 2001 and 2015, we estimate a 2SLS model that tests for this moderating role of education. We find support for a negative interaction effect of FDI and macro-level education on the rate of entrepreneurial activity, suggesting that in countries with highly educated labour forces, inward FDI leads to more jobs in the wage sector rather than a higher number of entrepreneurs. Policy implications are discussed.
PUBLISHED
Keywords: Entrepreneurial activity; Inward FDI; Spillover effects